Effect of Amperage and Field of View on Detection of Vertical Root Fracture in Teeth with Intracanal Posts - Safi, Yaser; Hosseinpour, Sepanta; Aziz, Alireza; Bamedi, Masoud; Malekashtari, Mahsa; Vasegh, Zahra (Iranian Endodontic Journal, 2016)
Introduction: This study sought to assess the effects of amperage (mA) and field of view (FOV) on intracanal metal post artifacts and the diagnostic parameters for detection of vertical root fracture (VRF) in teeth with intracanal posts. Methods and Materials: In this diagnostic study, 80 human single-canal teeth were evaluated by cone-beam computed tomography (CBCT). Nickel chrome cast posts were placed into root canals after root canal therapy and canal preparation. In the test group, fracture was induced by an instron machine while no fracture was induced in the control group. Deterministic and probabilistic sensitivity and specificity values at different exposure settings were statistically analyzed using the one-way ANOVA and pairwise comparisons were performed by Tukey’s test. Results: Significant differences were found between the two groups in terms of deterministic (P<0.0001) and probabilistic (P<0.013) sensitivity and deterministic (P<0.037) and probabilistic (P<0.0001) specificity at different FOV and mA combinations. Conclusion: A smaller FOV and lower mA should be preferably used for detection of VRFs in teeth with intracanal posts. Keywords: Amperage; Cone-Beam Computed Tomography; Field of View; Metal Artifact; Vertical Root Fracture